Application of logit model in innovation adoption: a study on biotechnology academic researchers in Malaysia - Farid, Hadi; Silong, Abu Daud; Sarkar, S. K. (IDOSI Publications, 2010)
Agro-biotechnology is considered as a strong potential to speed up the movement towards industrialization in Malaysia due to the country’s specific needs and social, geographical and industrial context. The level of adoption of agricultural biotechnology in Malaysia should be accelerated to change this potential to actual improve. Academic centers play a great role in Malaysian context because they are the main providers for biotechnology. The aim of this paper is to determine and optimize the technology adoption scenario in Malaysia from the viewpoint of academic researchers. Based on the previous studies the general predictors of the level of adoption are determined as six factors including level of knowledge, amount of funds, level of acceptance and receptiveness, level of cooperation, level of transfer of technology and personal characteristics. According to academic researchers, among the variables mentioned above, level of knowledge, acceptance and transfer of technology influence the level of adoption of biotechnology innovation in Malaysian agro-biotechnology companies. Therefore, to accelerate the adoption of new biotechnology innovations it is suggested that policy makers place greater emphasis on providing facilities to increase the level of knowledge, acceptance and technology transfer as a strategy to accelerate the rate of biotechnology adoption in Malaysia.